Scoping the international impact from four independent national dermatology trials. (1st June 2021) - Williams, H. C.; Rogers, N. K.; Chalmers, J. R.; Thomas, K. S.
Abstract: Background: Research impact describes whether and how research results in wider benefits to society beyond academic publication. Little is known about translation of clinical trial research into dermatological practice. Aim: We scoped international impact from four independently funded clinical trials published by our group over the past 10 years. Methods: This was a scoping survey of 35 international colleagues from 22 countries followed by a narrative summary of emergent themes. Results: All recipients kindly responded to the survey. At least 20 emergent themes were identified, which broadly included: (i) interest and enthusiasm in the concept of trying to document clinical trial impact; (ii) direct impacts such as adoption of the drug as tested and recommended from the trial results, including more confidence using the drug in slightly different ways for the same condition; (iii) the finding that trial impact was dependent on factors such as drug availability and country‐specific disease patterns; and (iv) the educational value of good trial design for journal club discussions and improving future clinical trial designs in dermatology. Our survey suggests that uptake into clinical practice was surprisingly rapid and widespread. Conclusion: Clinical trial research is of little use unless findings are translated into clinical practice for patient benefit. Our international scoping survey suggests that independent clinical trials that address important questions identified by the dermatology community have substantial, diverse and far‐reaching impacts on dermatological practice.